Counter-Hegemonic Forces, Language Choice, and Linguistic Needs in the Tobagonian Primary Classroom (London Journal of Research In Humanities and Social Sciences, 2025)
This study is anchored in postcolonial theory, which provides the critical lens through which the enduring impacts of colonial power structures on primary education in Trinidad and Tobago, specifically linguistic practices, were examined. The primary aim of the investigation was to ascertain what counter-hegemonic forces challenge the dominant language ideologies in the classroom in Tobago. A qualitative approach was deemed appropriate for this investigation and in order to acquire a profound understanding of the issues, in-depth interviews, semi-structured questionnaires and classroom observations were utilized for data collection. The participants comprised four teachers who are employed in a suburban school in Tobago. The data analysis process incorporated a thematic approach using a coding matrix. The results revealed that linguistic counter-hegemonic forces, particularly Creole, prevail amidst diversity and ambivalence in the classroom. It can be concluded that the counter-hegemonic influences serve to complement the linguistic dynamics required for teaching and learning. An analysis is recommended, to discern strengths, weaknesses, opportunities and solutions, so that teachers and students may be empowered and provided with adequate support.
Keywords: morality.; history; memory; Nietzsche; animality; forgetfulness; unhistorical; suprahistorical; overhuman; landscape; Archaeology; Lithics material culture; Serra Negra; Southern Espinha篠Range; linguistic diversity.; counter-hegemonic forces; language choice; linguistic needs; ambivalence.